2022
DOI: 10.1073/pnas.2207841119
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanoparticle-mediated lymph node–targeting delivery of mRNA cancer vaccine elicits robust CD8 + T cell response

Abstract: The targeted delivery of messenger RNA (mRNA) to desired organs remains a great challenge for in vivo applications of mRNA technology. For mRNA vaccines, the targeted delivery to the lymph node (LN) is predicted to reduce side effects and increase the immune response. In this study, we explored an endogenously LN-targeting lipid nanoparticle (LNP) without the modification of any active targeting ligands for developing an mRNA cancer vaccine. The LNP named 113-O12B showed increased and specific expression in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
171
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 34 publications
1
171
0
Order By: Relevance
“…Figures 4a and b show infiltration of both cytotoxic CD8 + and CD4 + T cells (green signals) in both tumor and spleen tissues in the IP-vaccinated group compared with the non-vaccinated group. Infiltration of cytotoxic CD8 + and CD4 + T cells in the tumor microenvironment is critical for tumor regression, as previously noted, [43][44][45][46] and these results demonstrate the ability of our IP-administered minimal mRNA vaccine to elicit cell-mediated adaptive immunity, which is considered a main element required for tumor clearance. Moreover, based on the unique features of the mRNA vaccines in stimulating both the cellular and humoral immunity we are expecting the ability of our minimal mRNA vaccine on stimulating the humoral immunity.…”
Section: Resultssupporting
confidence: 82%
“…Figures 4a and b show infiltration of both cytotoxic CD8 + and CD4 + T cells (green signals) in both tumor and spleen tissues in the IP-vaccinated group compared with the non-vaccinated group. Infiltration of cytotoxic CD8 + and CD4 + T cells in the tumor microenvironment is critical for tumor regression, as previously noted, [43][44][45][46] and these results demonstrate the ability of our IP-administered minimal mRNA vaccine to elicit cell-mediated adaptive immunity, which is considered a main element required for tumor clearance. Moreover, based on the unique features of the mRNA vaccines in stimulating both the cellular and humoral immunity we are expecting the ability of our minimal mRNA vaccine on stimulating the humoral immunity.…”
Section: Resultssupporting
confidence: 82%
“…In addition to their successful application in the local delivery of vaccines, LNPs have also enabled targeted delivery to organs via systematic administration [ 138 , 139 ]. This specificity of organ selectivity is mainly based on the global/obvious pK a of the lipid and serum protein interactions of selective organ-targeting (SORT) nanoparticles [ 140 ].…”
Section: Mrna Delivery Systemmentioning
confidence: 99%
“…Jinjin et al developed an LN targeting lipid (113-O12B), which was used to deliver an OVA-encoding mRNA cancer vaccine against a melanoma mouse model. In addition to exhibiting better expression in LNs compared with ALC-0315 (a synthetic lipid used in the COVID-19 vaccine Comirnaty), the vaccine also promoted mRNA expression in APCs, but the potential hepatotoxicity needs to be verified (75). Matthias et al found that incorporation of different adjuvants (LPS) will improve the potency of the lipid-based SANP mRNA vaccine, resulting in B16 F10 melanoma tumor shrinkage and extended survival of the tumor-bearing mouse (76).…”
Section: Lipid-based Sanpsmentioning
confidence: 99%